MANEJO TERAPÊUTICO DO PACIENTE COM DISFUNÇÃO OLFATÓRIA: REVISÃO DA LITERATURA - Bedaque, Henrique; Maria de Brito Macedo Ferreira, Lidiane; Juliane Patrícia Grigório da Silva; Mônica Claudino Medeiros Honorato; Deborah Carla Santos Gibson; Halan Araújo Santos; Lucas Marinho Vasconcelos (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: Olfactory dysfunction has been shown to be a very prevalent alteration in patients with COVID-19, both as a clinical presentation and as a sequel of duration not yet determined. Thus, this research seeks to understand how the new publications on the treatment of hyposmia and anosmia have brought therapeutic opportunities. Methodology: This is a literature review of articles published on the topic of olfactory dysfunction and treatment, in the MEDLINE + PUBMED database. The research was designed using the following descriptors: “hyposmia OR anosmia AND treatment”. Then the filters were used: “last 05 years” and “human”. In addition to the following types of study: “Clinical Trial”, “Systematic Review” and “Meta-analyzes”. Totaling 55 articles, of which we highlight 13 articles with consistent summary for the purpose of this review. Conclusion: Most of the recently published studies focus on treatment based on two interventions: the use of corticosteroids and olfactory training, showing good results but in fragile studies. In addition, therapeutic opportunities with the use of intranasal insulin, positive pressure devices and nasal lavage with sodium citrate have appeared in recent publications. Key words: Olfaction Disorders; Therapeutics; Drug therapy and Smell.